Manipulation and Characterization of Electrosprayed Ions Under Ambient Conditions : Methods and Instrumentation - Baird, Zane (Springer International Publishing : Imprint: Springer, 2017)
This thesis addresses the evolving field of measurement science, specifically that of mass spectrometry (MS) and ion mobility spectrometry (IMS) based techniques. It focuses on the design, construction and implementation of low-cost, easy-to-manufacture measurement tools that are used in modern settings such as airport security screening. Advances in these technologies often involve minimal performance enhancement at ever-increasing cost, which in turn limits accessibility to versatile measurement tools. This problem is addressed using desktop 3D printers along with widely available materials for the production of novel ion lenses and an IMS instrument with a performance comparable to that of many commercial systems. Baird´s findings are a source of inspiration for scientists exploring this emerging field.
Keywords: Chemistry.; Mass spectrometry.; Spectroscopy.; Physical chemistry.; Microscopy.; elektronické knihy; electronic books